Species diversity and conservation status of ornamental fish traded in Kupang, East Nusa Tenggara, Indonesia - ZAINAL USMAN; DIMAS RIZKY HARIYADI; LUKAS G. G. SERIHOLLO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Usman Z, Hariyadi DR, Serihollo LGG. 2024. Species diversity and conservation status of ornamental fish traded in Kupang, East Nusa Tenggara, Indonesia. Biodiversitas 25: 1116-1126. The high demand for ornamental fish native to Indonesia has the potential to be used as a source of foreign exchange income. In addition to increasing the national income, the ornamental fish trade must also be considered to preserve the population of the fish species being sold. The study aimed to determine ornamental fish diversity and conservation status in Kupang City, East Nusa Tenggara. This research was conducted in Kupang City, East Nusa Tenggara, Indonesia, from August to September 2023. The research was conducted using survey (non-experiment) and observation methods. The survey method was carried out using a form to conduct interviews with sellers in 11 ornamental fish shops. At the same time, the observation method was used to identify the types of fish being traded. The study's results recorded 18 families, 39 genera, and 46 fish species (Include 1 species is hybrid fish). The highest species diversity came from the Cichlidae family with 9 species (1 species (Amphilophus citrinellus x Cichlasoma trimaculatum) is hybrid fish), followed by Cyprinidae with 7 species, whereas each species of the Characidae and Poecilidae families were 5 species. Conservation status shows 4 status groupings, namely Least Concern (LC), Vulnerable (VU), Endangered (EN), and Not Evaluated (NE). Based on these groupings, there were 32 species in the Least Concern (LC) category, 3 species in the Endangered (EN) category, 2 species in the Vulnerable (VU) category, and 8 species in the Not Evaluated (NE) and 1 unclassified category. There is only 1 species that is included in the Appendix I category, namely Scleropages formosus, and other species are Not evaluated. This is the first study conducted in Kupang City to reveal the types of ornamental fish species sold and their conservation status. The study will be useful information to the government, researchers, and other stakeholders on the potential extinction risk of each type of fish being traded.